A Valsa mali Effector Protein 1 Targets Apple (Malus domestica) Pathogenesis-Related 10 Protein to Promote Virulence - Wang, Weidong; Nie, Jiajun; Lv, Luqiong; Gong, Wan; Wang, Shuaile; Yang, Mingming; Xu, Liangsheng; Li, Mingjun; Du, Hongxia; Huang, Lili (Frontiers in Plant Science, 2021)
To successfully colonize plants, pathogenic microbes secrete a mass of effector proteins to manipulate host immunity. Apple valsa canker is a destructive disease caused by the weakly parasitic fungus Valsa mali. Previous study indicated that the Valsa mali effector VmEP1 is an essential virulence factor. However, the pathogenic mechanism of VmEP1 in V. mali remains poorly understood. In this study, we found that the apple (Malus domestica) pathogenesis-related 10 proteins (MdPR10) is a virulence target of VmEP1 using a yeast two-hybrid screening. By bimolecular fluorescence (BiFC) and coimmunoprecipitation (Co-IP), we confirmed that VmEP1 interacts with MdPR10 in vivo. Silencing of MdPR10 notably enhanced V. mali infection, and overexpression of MdPR10 markedly reduced its infection, which corroborates its positive role in plant immunity against V. mali. Furthermore, we showed that co-expression of VmEP1 with MdPR10 compromised the MdPR10-mediated resistance to V. mali. Taken together, our results revealed a mechanism by which a V. mali effector protein suppresses host immune responses, likely by interfering with the MdPR10-mediated resistance to V. mali during infection.